Guidelines towards information-driven mobility management - Sofia, R. C. (2019)
The architectural semantics of Information-Centric Networking bring in interesting features in regards to mobility management: Information-Centric Networking is content-oriented, connection-less, and receiver-driven. Despite such intrinsic advantages, the support for node movement is being based on the principles of IP solutions. IP-based solutions are, however, host-oriented, and Information-Centric Networking paradigms are information-oriented. By following IP mobility management principles, some of the natural mobility support advantages of Information-Centric Networking are not being adequately explored. This paper contributes with an overview on how Information-Centric Networking paradigms handle mobility management as of today, highlighting current challenges and proposing a set of design guidelines to overcome them, thus steering a vision towards a content-centric mobility management approach.